Effect of early hospital readmission and comorbid conditions on subsequent long‐term mortality after transient ischemic attack. Issue 12 (22nd November 2017) - Yousufuddin, Mohammed; Young, Nathan; Keenan, Lawrence; Olson, Tammy; Shultz, Jessica; Doyle, Taylor; Ahmmad, Eimad; Arumaithurai, Kogulavadanan; Takahashi, Paul; Murad, Mohammad Hassan
Abstract: Background: The implications of early readmission on long‐term mortality after transient ischemic attack (TIA) are not known. We aimed at examining the effect of 180‐day readmission on subsequent long‐term mortality after index hospitalization for TIA. Methods: A retrospective study of patients hospitalized for first‐ever TIA at Mayo Clinic from 2000 through 2017. Patients readmitted within 180 days postdischarge were compared with those not readmitted in long‐term risk of death. Results: Of 251 TIA patients aged 73 ± 15 years with 1509 person‐years of follow‐up, 65 (26%) were readmitted within 180 days of discharge and 125 died during a median follow‐up of 5.7 years. The mortality was 10 vs. 7 deaths per 100 person‐years in patients who were readmitted compared to those who were not readmitted with hazard ratio (HR) 1.73 (95% confidence interval [CI] 1.13–2.66). Other competing predictors of mortality were age ≥65 years (HR 5.70, 95% CI 2.72–11.96), cancer (HR 1.65, 95% CI 1.03–3.38), chronic obstructive pulmonary disease (HR 1.90, 95% CI 1.07–3.38), heart failure (HR 3.03, 95% CI 1.82–5.06), dementia (HR 5.87, 95% CI 3.27–10.52), creatinine ≥1.4 mg/dl (HR 1.89, 95% CI 1.17–3.06), and hemoglobin level <10 g/dl (HR 2.80, 95% CI 1.20–6.66). Conclusions: Hospital readmission within 180 days of discharge from index TIA was associated with increased risk of death several years after initial readmission. Older age and several comorbidities identified during index hospitalization also confer increased risk for long‐term mortality. Abstract : Implications of early readmission on long‐term mortality after transient ischemic attack (TIA) are not known. In this retrospective analysis of 251 patients hospitalized for TIA and who were followed up over a median period of 5.7 years, we demonstrated that hospital readmission within 180 days of discharge following TIA was associated with increased risk of death several years after initial readmission.